Perbedaan Tingkat Stres Mahasiswa Perantauan dan Bukan Perantauan - Eka Handayani; Novita Nirmalasari (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
The students who study in the Faculty of Health of Universitas Jenderal Achmad Yani Yogyakarta come from various area in Indonesia. Various socio-cultural aspects and academic aspects may cause some problems. It can make difficult for them to adapt with the environment which eventually make them stressful. This study aimed to find out the stress level difference between overseas students and domestic students. This study used a comparative descriptive design recruiting 188 respondens by stratified random sampling technique. Data were collected by using perceived of stress scale questionnaire. Data were analyzed using Chi square test. The results of this study showed that of 13(6,92%) female respondens who had severe stress. Domestic students tend to experience mild stress, which is 76 (80.85%) but overseas student more often severe stress 10 (10.64%). Students from Medical Records had more often mild stress 33 (17.55%). Data were analyzed using Chi Square test. The results showed that there were no significant differences in the stress level between overseas students and domestic students (p>0.05) Keywords: domestic students; overseas students; stress ABSTRAK Mahasiswa Fakultas Kesehatan Universitas Jenderal Achmad Yani Yogyakarta berasal dari berbagai daerah di Indonesia. Perbedaan sosial, budaya dan sistem pembelajaran akan menimbulkan masalah bagi mahasiswa perantauan dan bukan perantauan. Masalah tersebut dapat memicu stres pada mahasiswa. Penelitian ini bertujuan untuk mengetahui perbedaan tingkat stres mahasiswa perantauan dan bukan perantauan. Penelitian ini menggunakan desain deskriptif komparatif. Teknik pengambilan sampel menggunakan stratified random sampling dengan jumlah 188 mahasiswa. Teknik pengambilan data menggunakan kuesioner Perceived of Stress Scale. Uji statistik menggunakan Chi square. Hasil penelitian didapatkan bahwa responden berjenis kelamin perempuan mengalami stres berat sebanyak 13(6,92%). Mahasiswa bukan perantauan mengalami stres sedang sebanyak 76(80,85%). Mahasiswa perantauan lebih banyak mengalami stres berat sebanyak 10(10,64%). Jurusan Rekam Medis merupakan jurusan dengan mahasiswa yang paling banyak mengalami stres sedang sebanyak 33(17,55%). Hasil penelitian menunjukkan bahwa tidak ada perbedaan tingkat stres mahasiswa perantauan dan bukan perantauan di Fakultas Kesehatan Unjani Yogyakarta (p>0,05). Keywords: mahasiswa bukan perantauan; mahasiswa perantauan; stres